2023
DOI: 10.1093/ckj/sfad007
|View full text |Cite
|
Sign up to set email alerts
|

Sodium-glucose cotransporter-2 inhibitor therapy in kidney transplant patients with type 2 or post-transplant diabetes: an observational multicentre study

Abstract: Background Sodium-glucose cotransporter-2 inhibitors (SGLT2i) have cardioprotective and renoprotective effects. However, experience with SGLT2i in diabetic kidney transplant recipients (DKT) is limited. Methods This observational multicentre study was designed to examine the efficacy and safety of SGLT2i in DKTR. The primary outcome was adverse effects within 6 months of SGLT2i treatment. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(59 citation statements)
references
References 42 publications
1
58
0
Order By: Relevance
“…A meta-analysis performed by Chewcharat et al involving 6 of these studies with 82 KTRs did not demonstrate a clinically significant decline in blood pressure-SBP (WMD = 3.24 mmHg [95% CI: 7.92, 1.45]; P = 0.18) and DBP (WMD = 1.49 mmHg [95% CI: 3.81, 0.83]; P = 0.21) [47]. However, two recently published observational studies by Carro et al and Fructuoso et al reported clinically significant reduction in mean blood pressure readings in 323 and 339 patients respectively [30,43]. Some of these studies already had patients on various anti-hypertensive agents [56 ▪▪ ] and only included office blood pressure measurements instead of ambulatory blood pressure readings.…”
Section: Current Evidence Regarding the Role Of Sodium-glucose Cotran...mentioning
confidence: 94%
See 3 more Smart Citations
“…A meta-analysis performed by Chewcharat et al involving 6 of these studies with 82 KTRs did not demonstrate a clinically significant decline in blood pressure-SBP (WMD = 3.24 mmHg [95% CI: 7.92, 1.45]; P = 0.18) and DBP (WMD = 1.49 mmHg [95% CI: 3.81, 0.83]; P = 0.21) [47]. However, two recently published observational studies by Carro et al and Fructuoso et al reported clinically significant reduction in mean blood pressure readings in 323 and 339 patients respectively [30,43]. Some of these studies already had patients on various anti-hypertensive agents [56 ▪▪ ] and only included office blood pressure measurements instead of ambulatory blood pressure readings.…”
Section: Current Evidence Regarding the Role Of Sodium-glucose Cotran...mentioning
confidence: 94%
“…They reported no differences in the trough levels of tacrolimus, cyclosporine, and everolimus at 24 weeks when compared to baseline [42]. A recent multicenter study following 225 KTRs for 12 months reported that the tacrolimus and mycophenolate levels were not significantly altered by the use of SGLT2i for 6 months in KTRs [43]. Based on small studies of KTRs, co-utilization of SGLT2i with immunosuppressive agents did not seem to alter the pharmacokinetics of the latter.…”
Section: Mechanisms Of Action Of Sodium-glucose Cotransporter 2 Inhib...mentioning
confidence: 97%
See 2 more Smart Citations
“…reported the largest observational multicenter study involving 339 diabetic KTRs. 25 The primary outcome was the incidence of UTI during first 6 months of using SGLT2i. They reported 13.6% of the patients having at least one episode of UTI during the 6 months prior to introduction of SGLT2i drugs.…”
Section: Evaluation Of the Sglt2i Groupmentioning
confidence: 99%